Detecting of Gunshots Direction Using TDOA (Time Difference of Arrival) - Untsa, Risdilah Mimma; Akbar, Fannush Shofi; Faradila Purnama, Arrizky Ayu; Muhsin, M; Rachmaningrum, Nilla (Emitor: Jurnal Teknik Elektro, 2025)
In order to avoid shots being fired in undesirable areas, a device is required that can detect the origin of the shot so that the source of the bullet can be identified. This research was conducted to maintain the security and stability of a region. The objective of this study is to develop a device that utilizes the time difference of arrival (TDoA) method to determine the direction of gunshot on a gunshot location device. Prior to the implementation of TDoA, the received sound undergoes a filtration process utilizing an FIR filter. The filtered sound is then subjected to the time-of-arrival (TDoA) method. This method involves the comparison of the direction of sound arrival, followed by calculation and conversion to determine the origin of the gunshot sound. The TDoA coordinates are subsequently determined through the utilization of the multilateration method. In the experiments conducted using a speaker as the sound source and four microphones as receiving sensors, changing the speaker's location demonstrated that the signal-to-noise ratio (SNR) of the sound signal increased as the distance between the sensor and the sound source decreased. Furthermore, the implementation of an FIR filter during post-processing can enhance the SNR of the sound received at the sensor by 27% to 32%. In this research, the TDoA method demonstrated a high degree of efficacy, attaining a detection accuracy of 99.78%.